Investigation of University Students’ Opinions on the Power Exercised by Teachers in EFL Classes: The Case of Türkiye - Burcu Karafil; Osman Özdemir (Journal of Educational Issues, 2024)
The aim of this study is to examine the students’ opinions on the power exercised by their teachers in the EFL classes in Türkiye. The participants of the study, which was designed as a survey method, consisted of 243 university students. To collect the data, the “Teacher Power Use Scale” was developed. The scale was developed in three stages. The results obtained supported a five-factor structure consisting of 36 items. The factors were named as “expert power”, “reward power”, “referent power”, “coercive power” and “legitimate power”, respectively. Descriptive statistics were computed to display the students’ overall responses to the Teacher Power Use Scale. T-test was conducted to determine whether there were any significant differences in gender variable. One-way ANOVA was conducted to investigate whether there were any differences in the opinions of students on the teacher power exercises in terms of attending office hours, and accessibility of EFL teachers variables. It was obtained that teachers exercised expert power, referent power at high level while they exercised reward power, coercive power and legitimate power at moderate level. There was a significant difference in the coercive power dimension in terms of students’ opinions on the power exercises in the classroom in favor of male students. Attending office hour was not a significant variable in terms of students’ opinions on the power exercised by their teachers. Finally, the scores obtained from the scale differed significantly in the dimensions of the scale except for the coercive power and legitimate power according to the accessibility level of EFL teachers.